2022
DOI: 10.1021/acsomega.2c01681
|View full text |Cite
|
Sign up to set email alerts
|

1-O-Actylbritannilactone Ameliorates Alcohol-Induced Hepatotoxicity through Regulation of ROS/Akt/NF-κB-Mediated Apoptosis and Inflammation

Abstract: 1- O -Acetylbritannilactone (ABL) is a marker component of Inula britannica L. and is reported to exhibit multiple pharmacological activities, including antiaging, anti-inflammatory, and antidiabetic properties. Although the protective effect of Inula britannica L. on animal models of liver injury has been widely reported, the effect of ABL on alcohol-induced liver damage has not been confirmed. The present study was designed to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Drinking alcohol leads to impaired antioxidant defenses and overproduction of ROS. Alcohol-induced ROS production is mediated by the downregulation of Akt, which enhances the activation of NF-κB and ultimately stimulates the release of inflammatory cytokines TNF-α and IL-1β . Recent literature suggests that ROS concentration, especially in the mouth cavity, is significantly higher during alcohol consumption than that in the case of serum. , An amazing fact is that the increase in ROS production is led by the increased activity of phospholipase A1 and A2 because the increased amount of superoxide anion production in mitochondria happens not only in chronic drinking but also during taking one dose …”
Section: Sources Of Rosmentioning
confidence: 99%
“…Drinking alcohol leads to impaired antioxidant defenses and overproduction of ROS. Alcohol-induced ROS production is mediated by the downregulation of Akt, which enhances the activation of NF-κB and ultimately stimulates the release of inflammatory cytokines TNF-α and IL-1β . Recent literature suggests that ROS concentration, especially in the mouth cavity, is significantly higher during alcohol consumption than that in the case of serum. , An amazing fact is that the increase in ROS production is led by the increased activity of phospholipase A1 and A2 because the increased amount of superoxide anion production in mitochondria happens not only in chronic drinking but also during taking one dose …”
Section: Sources Of Rosmentioning
confidence: 99%
“…Apoptosis induced by Aβ25-35 may be due to the activation of an intracellular apoptotic cascade, including the activation of Bax in hippocampus neurons. Exposure to Aβ25-35 induced a significant increase in the relative expression of Bax/Bcl-2 [50]. The pro-apoptotic factor Bax and the anti-apoptotic factor Bcl-2 cause mitochondrial membrane permeability in vitro, which is a key pathway of mitochondrial apoptosis [51].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, our molecular docking results illustrated that ligand GRb1 exhibited a strong binding affinity with Caspase3 and Bcl‐2. Evidence has suggested that apoptosis of hepatocytes is a critical mechanism of liver injury 32,33 . On this basis, western blotting analysis was conducted in the subsequent in vivo experiment to validate the apoptosis pathway‐related proteins Caspase3, Caspase8, Bax and Bcl‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has suggested that apoptosis of hepatocytes is a critical mechanism of liver injury. 32,33 On this basis, western blotting analysis was conducted in the subsequent in vivo experiment to validate the apoptosis pathway-related proteins Caspase3, Caspase8, Bax and Bcl-2. As a critical protease, Caspase-8 participates in extrinsic apoptosis signal transduction, while caspase-3 is crucial for apoptosis execution.…”
Section: Integrated Network Analysis To Elucidate the Protective Mech...mentioning
confidence: 99%